Deaf-Blind - McCullagh, Jennifer; Weiss, Deborah (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Screening Test for Auditory Processing Disorders - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Pediatric Speech Intelligibility Test - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Otitis Media - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Hearing - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Dichotic Listening - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Deafness - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Cochlea - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Brainstem Audiometry - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Auditory Brainstem Response, ABR - McCullagh, Jennifer (Encyclopedia of Autism Spectrum Disorders, 2013)
Keywords: dept.cmd

Measures of binaural interaction - McCullagh, Jennifer; Bamiou, Doris (Handbook of (Central) Auditory Processing Disorders: Auditory neuroscience and diagnosis, 2013)
Keywords: dept.cmd

More than words - Wallace, S.; Purdy, M. (ASHA Leader, 2013)
Keywords: dept.cmd

Identification of Conductive Hearing Loss in Young Infants Using Tympanometry and Wideband Reflectance. - Prieve, Beth; Vander Werff, Kathy; Preston, Jonathan; Georgantas, Lea (Ear and Hearing, 2013)
Objective: The goal of the study was to evaluate the effectiveness of tympanometry and wideband reflectance (WBR) in detecting conductive hearing loss (CHL) in young infants., Methods: Type of hearing loss was determined using auditory brainstem response using air- and bone-conducted tone bursts in 84 ears from 70 infants (median age = 10 weeks). Of these 84 ears, 60 are included in the current analysis: 43 with normal hearing (NH) and 17 with CHL. Tympanometry was measured using probe tone frequencies of 226, 678, and 1000 Hz. Tympanograms were evaluated in two ways: (1) Acoustic middle ear admittance (Ya, in millimhos); and (2) two-category classification (normal/abnormal), as described by Baldwin (2006). Measures of Ya were evaluated in two ways: by admittance-magnitude tympanograms and calculated admittance magnitude from subcomponents (conductance and susceptance). WBR was measured in response to a chirp stimulus after probe calibration. WBR was analyzed into thirteen 1/3 octave bands. Tests for statistical differences for two-category classification were analyzed using Chi-squared and Ya, and WBR were analyzed using repeated-measures analyses of variances. Cohen's d and likelihood ratios were computed for comparison with statistically significant differences., Results: Ya measured with 678- and 1000 Hz probe tones was significantly different between ears with CHL and NH. Two-category classification of tympanograms using a 1000 Hz probe tone was significantly different between ears with CHL and NH. Neither two-category classification nor Ya was significantly different between ears identified with CHL and NH using a 226 Hz probe tone. WBR was significantly higher in the frequency bands 800 to 2500 Hz and in the frequency band centered at 6300 Hz in infants with CHL. Effect sizes (Cohen's d) were greater than 2 for several WBR frequency bands and Ya measured with 1000 Hz probe tones. The results were similar for calculations of Ya from admittance-magnitude and subcomponent tympanograms. Positive likelihood ratios for WBR ranged between 8.1 and 38, and those for Ya using 1000 Hz ranged between 12.5 and 32., Conclusions: CHL in young infants can be detected well with WBR or tympanometry using probe frequencies of 678 and 1000 Hz., (C) 2013 by Lippincott Williams & Wilkins
Keywords: Acoustic Impedance Tests; Acoustic Stimulation; Evoked Potentials, Auditory, Brain Stem; Female; Hearing Loss, Conductive; Hearing Tests; Humans; Infant; Infant, Newborn; Likelihood Functions; Male; Sensitivity and Specificity; acoustic impedance; article; auditory stimulation; conduction deafness; dept.cmd; evoked brain stem auditory response; female; hearing test; human; infant; male; methodology; newborn; sensitivity and specificity; statistical model

Ultrasound biofeedback treatment for persisting childhood apraxia of speech - Preston, Jonathan L.; Brick, Nickole; Landi, Nicole (American Journal of Speech-language Pathology, 2013)
Purpose: The purpose of this study was to evaluate the efficacy of a treatment program that includes ultrasound biofeedback for children with persisting speech sound errors associated with childhood apraxia of speech (CAS). Method: Six children ages 9-15 years participated in a multiple baseline experiment for 18 treatment sessions during which treatment focused on producing sequences involving lingual sounds. Children were cued to modify their tongue movements using visual feedback from real-time ultrasound images. Probe data were collected before, during, and after treatment to assess word-level accuracy for treated and untreated sound sequences. As participants reached preestablished performance criteria, new sequences were introduced into treatment. Results: All participants met the performance criterion (80% accuracy for 2 consecutive sessions) on at least 2 treated sound sequences. Across the 6 participants, performance criterion was met for 23 of 31 treated sequences in an average of 5 sessions. Some participants showed no improvement in untreated sequences, whereas others showed generalization to untreated sequences that were phonetically similar to the treated sequences. Most gains were maintained 2 months after the end of treatment. The percentage of phonemes correct increased significantly from pretreatment to the 2-month follow-up. Conclusion: A treatment program including ultrasound biofeedback is a viable option for improving speech sound accuracy in children with persisting speech sound errors associated with CAS.
Keywords: Adolescent; Apraxias; Articulation; Biofeedback, Psychology; Child; Childhood apraxia of speech; Children; Cues; Efficacy; Feedback, Sensory; Follow-Up Studies; Humans; Intervention; Male; Phonetics; Speech; Speech Disorders; Speech Therapy; Speech sound disorders; Tongue; Treatment Outcome; Ultrasonic Therapy; adolescent; apraxia; article; articulation; association; child; childhood apraxia of speech; children; clinical trial; dept.cmd; echography; efficacy; follow up; human; intervention; male; methodology; pathophysiology; phonetics; physiology; psychophysiology; sensory feedback; speech; speech disorder; speech sound disorders; speech therapy; tongue; treatment outcome; ultrasound therapy

Toward improved spectral measures of /s/: results from adolescents - Koenig, Laura L.; Shadle, Christine H.; Preston, Jonathan L.; Mooshammer, Christine R. (Journal of Speech Language and Hearing Research, 2013)
Purpose: This article introduces theoretically driven acoustic measures of /s/ that reflect aerodynamic and articulatory conditions. The measures were evaluated by assessing whether they revealed expected changes over time and labiality effects, along with possible gender differences suggested by past work. Method: Productions of /s/ were extracted from various speaking tasks from typically speaking adolescents (6 boys, 6 girls). Measures were made of relative spectral energies in low-(550-3000 Hz), mid-(3000-7000 Hz), and high-frequency regions (7000-11025 Hz); the mid-frequency amplitude peak; and temporal changes in these parameters. Spectral moments were also obtained to permit comparison with existing work. Results: Spectral balance measures in low-mid and mid-high frequency bands varied over the time course of /s/, capturing the development of sibilance at mid-fricative along with showing some effects of gender and labiality. The mid-frequency spectral peak was significantly higher in nonlabial contexts, and in girls. Temporal variation in the mid-frequency peak differentiated +/- labial contexts while normalizing over gender. Conclusions: The measures showed expected patterns, supporting their validity. Comparison of these data with studies of adults suggests some developmental patterns that call for further study. The measures may also serve to differentiate some cases of typical and misarticulated /s/.
Keywords: Acoustics; Adolescent; Adolescents; Development; Female; Humans; Lip; Male; Phonetics; Reference Values; Sex Characteristics; Speech; Speech Acoustics; Speech production; Verbal Behavior; acoustics; adolescent; adolescents; article; comparative study; dept.cmd; development; female; human; lip; male; phonetics; reference value; sexual development; speech; speech production; verbal behavior

Preschool speech error patterns predict articulation and phonological awareness outcomes in children with histories of speech sound disorders. - Preston, Jonathan L; Hull, Margaret; Edwards, Mary Louise (American journal of speech-language pathology, 2013)
Purpose: To determine if speech error patterns in preschoolers with speech sound disorders (SSDs) predict articulation and phonological awareness (PA) outcomes almost 4 years later. Method: Twenty-five children with histories of preschool SSDs (and normal receptive language) were tested at an average age of 4;6 (years;months) and were followed up at age 8;3. The frequency of occurrence of preschool distortion errors, typical substitution and syllable structure errors, and atypical substitution and syllable structure errors was used to predict later speech sound production, PA, and literacy outcomes. Results: Group averages revealed below-average schoolage articulation scores and low-average PA but ageappropriate reading and spelling. Preschool speech error patterns were related to school-age outcomes. Children for whom >10% of their speech sound errors were atypical had lower PA and literacy scores at school age than children who produced <10% atypical errors. Preschoolers who produced more distortion errors were likely to have lower school-age articulation scores than preschoolers who produced fewer distortion errors. Conclusion: Different preschool speech error patterns predict different school-age clinical outcomes. Many atypical speech sound errors in preschoolers may be indicative of weak phonological representations, leading to long-term PA weaknesses. Preschoolers' distortions may be resistant to change over time, leading to persisting speech sound production problems. © American Speech-Language-Hearing Association.
Keywords: *Articulation Disorders/di [Diagnosis]; *Language Tests; *Phonetics; *Speech; *Speech Articulation Tests; Awareness; Child; Child Language; Child, Preschool; Female; Follow-Up Studies; Humans; Language Disorders/di [Diagnosis]; Literacy; Male; Outcomes; Phonological awareness; Predictive Value of Tests; Psycholinguistics; Reading; Speech Production Measurement; Speech Sound Disorder; Speech production; Speech sound disorders; dept.cmd

The relationship between phonological and auditory processing and brain organization in beginning readers - Pugh, Kenneth R.; Landi, Nicole; Preston, Jonathan L.; Mencl, W. Einar; Austin, Alison C.; Sibley, Daragh; Fulbright, Robert K.; Seidenberg, Mark S.; Grigorenko, Elena L.; Constable, R. Todd; Molfese, Peter; Frost, Stephen J. (Brain and Language, 2013)
We employed brain-behavior analyses to explore the relationship between performance on tasks measuring phonological awareness, pseudoword decoding, and rapid auditory processing (all predictors of reading (dis)ability) and brain organization for print and speech in beginning readers. For print-related activation, we observed a shared set of skill-correlated regions, including left hemisphere temporoparietal and occipitotemporal sites, as well as inferior frontal, visual, visual attention, and subcortical components. For speech-related activation, shared variance among reading skill measures was most prominently correlated with activation in left hemisphere inferior frontal gyrus and precuneus. Implications for brain-based models of literacy acquisition are discussed. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Awareness; Brain; Brain Mapping; Child; Child, Preschool; Decoding; FMRI; Female; Humans; Individual differences; Male; Phonological awareness; Photic Stimulation; Psychomotor Performance; Rapid auditory processing; Reading; Speech; Speech Perception; Thalamus; Visual Perception; article; attention; child; dept.cmd; female; frontal lobe; hearing; human; human experiment; inferior frontal gyrus; left hemisphere; male; neurophysiology; normal human; occipital lobe; parietal lobe; phonetics; precuneus; preschool child; printing; reading; school child; speech; task performance; temporal lobe; visual cortex; word recognition

Auditory cortical processing in noise in younger and older adults - Mccullagh, Jennifer; Shinn, Jennifer B (Hearing, Balance and Communication, 2013)
Objective: A common clinical complaint among older adults is difficulty hearing in noise, even in those with normal or near-normal peripheral hearing sensitivity. Researchers have demonstrated behavioral hearing in noise deficits in older adults, but to date limited evidence, particularly objective, exists elucidating the effects of age on auditory cortical processing in noise. The purpose of this investigation was to explore age related differences in auditory cortical processing at multiple signal-to-noise ratios (SNRs). Study design: Twenty normal-hearing young adults and 15 normal-hearing older adults participated in the study. Late auditory evoked potential (N1 and P2) latencies and amplitudes were measured in quiet and at three signal-to-noise ratios (SNRs) (+ 20, + 10, and 0 SNR). Repeated measures analyses of variance (ANOVA) were utilized to determine if statistically significant differences existed. Results: Significant group by listening condition interactions existed for N1 and P2 amplitudes. P2 latencies were significantly longer for the older adult group compared to the younger adult group. In addition, N1 and P2 amplitudes were significantly smaller for the younger adult group compared to the older adult group. Conclusion: Results suggest a possibly greater reduction in the synchronous neuronal response from quiet to noisy conditions in older adults than in younger adults. © 2013 Informa Healthcare.
Keywords: Aging; Auditory late potentials; Hearing in noise; N1; P2; dept.cmd; peer-reviewed